2023
DOI: 10.1108/itp-03-2022-0207
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and outcomes of social media fatigue

Abstract: PurposeThis study aims to explore which of four chosen factors (i.e. privacy concerns, FoMO, self-disclosure and time cost) induce a feeling of strain among Facebook users in terms of social media fatigue (SMF), and if this occurs, whether it further influences such outcomes as discontinuance of usage (DoU) and interaction engagement decrement (IED).Design/methodology/approachThrough an online structured questionnaire, empirical data were gathered to verify the research model, based on the stressor-strain-outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…on well-being) and a larger set of behavioral brand-related responses beyond lurking (such as avoiding or unfollowing brands). Moreover, prior research has identified privacy concerns as a contributing factor to SMF (Bright et al, 2022;Baj-Rogowska, 2023) and as one of the main reasons for feelings of advertising intrusiveness (Youn and Kim, 2019). As such, ads may be perceived as intrusive not only because they interrupt the "flow" of social media activities (Dodoo and Wen, 2021) but also because they interfere with one's right to privacy (Mpinganjira and Maduku, 2019;Fernandes and Pereira, 2021), thus engendering negative psychological reactions that lead to fatigue.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…on well-being) and a larger set of behavioral brand-related responses beyond lurking (such as avoiding or unfollowing brands). Moreover, prior research has identified privacy concerns as a contributing factor to SMF (Bright et al, 2022;Baj-Rogowska, 2023) and as one of the main reasons for feelings of advertising intrusiveness (Youn and Kim, 2019). As such, ads may be perceived as intrusive not only because they interrupt the "flow" of social media activities (Dodoo and Wen, 2021) but also because they interfere with one's right to privacy (Mpinganjira and Maduku, 2019;Fernandes and Pereira, 2021), thus engendering negative psychological reactions that lead to fatigue.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Outcomes of SMF may be detrimental for both individuals and brands. For individuals, fatigue can affect well-being and trigger mental health problems (Baj-Rogowska, 2023). For brands, SMF is associated to a decrease in social media engagement, with users paying less attention to brand messages and becoming more selective about their media exposure, thus negatively impacting brands' performance.…”
Section: Introductionmentioning
confidence: 99%
“…Centralization in managing identities and authentication, while simplifying the login process, also increases the risk of unauthorized access to sensitive information [10]. The IdP, in traditional SSO systems, has the ability to track all the Service Providers (SPs) a user visits, potentially compromising user privacy [11].…”
Section: Privacy Concerns In Traditional Sso Systemsmentioning
confidence: 99%